Can Previous Pro-Environmental Behaviours Influence Subsequent Environmental Behaviours? The Licensing Effect of Pro-Environmental Behaviours. (5th December 2016) - Geng, Liuna; Cheng, Xiao; Tang, Zhuxuan; Zhou, Kexin; Ye, Lijuan
Methods for promoting individuals' pro-environmental behaviours are becoming very important. Besides traditional factors relevant to pro-environmental actions, few studies have examined the licensing effect within this domain. Across three studies we have explored whether the licensing effect really exists in pro-environmental behaviours, how this effect actually works, and how to inhibit or even avoid this effect. Results have revealed that previous pro-environmental behaviours lead to a decrease in subsequent pro-environmental behaviours, indicating a licensing effect. Also, the licensing effect in pro-environmental behaviours can be explained by having individuals focus on goal progress and reduced by focusing on goal commitment. Furthermore, attributional recall could be an intervention for mitigating the licensing effect.